2014
DOI: 10.1016/j.ygyno.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of universal MSI/IHC in screening ENDOMETRIAL cancer patients for lynch syndrome

Abstract: Objective Determine factors impacting the uptake of genetic counseling and results of genetic testing following universal tumor testing for Lynch syndrome in patients with endometrial cancer. Methods The study population consisted of two unselected cohorts of endometrial cancer patients, 408 identified retrospectively and 206 identified prospectively. Immunohistochemistry for mismatch repair protein expression and/or microsatellite instability analysis was performed on these tumors. MLH1 methylation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 25 publications
(38 reference statements)
1
65
0
2
Order By: Relevance
“…Specifically, we found that microsatellite instability and subsequent mutations in mismatch repair genes compatible with HNPCC are present in 40% of women. This is significantly higher than what has been reported in unselected populations of women with EC, where HNPCC is found in 9-11% of women (21). Therefore, despite the low number of SEOC patients in the literature analyzed for HNPCC mutations, HNPCC screening in all women with SEOC seems reasonable.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Specifically, we found that microsatellite instability and subsequent mutations in mismatch repair genes compatible with HNPCC are present in 40% of women. This is significantly higher than what has been reported in unselected populations of women with EC, where HNPCC is found in 9-11% of women (21). Therefore, despite the low number of SEOC patients in the literature analyzed for HNPCC mutations, HNPCC screening in all women with SEOC seems reasonable.…”
Section: Discussionmentioning
confidence: 56%
“…In unselected populations of women with EC, HNPCC is found in 9 to 11% of women (21). Young women with EC, especially those with SEOC, may even have a higher prevalence of HNPCC, although the exact rate of HNPCC in this subpopulation of women with EC is unknown.…”
mentioning
confidence: 99%
“…In some studies, the methylation assay was replaced by a clinical refinement method based on MLH1 germline mutation carrier characteristics such as young age at onset and extensive family history (Backes et al 2009(Backes et al , 2011, but the validity of this tactic has yet to be verified. Of the patients recommended to undergo genetic counseling, only 20-50% actually do so (Backes et al 2009;Batte et al 2014). The reasons not to accept genetic analyses (genetic counseling/genetic testing) primarily include medical cost, anxiety over the results, lack of risk awareness, and indifference to hereditary cancers (Backes et al 2011;Batte et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients recommended to undergo genetic counseling, only 20-50% actually do so (Backes et al 2009;Batte et al 2014). The reasons not to accept genetic analyses (genetic counseling/genetic testing) primarily include medical cost, anxiety over the results, lack of risk awareness, and indifference to hereditary cancers (Backes et al 2011;Batte et al 2014). To promote genetic analyses and proactive medical interventions, the following is required: subsidization of the medical cost, privacy protection, consolidation of medical knowledge, and the availability of an established information system.…”
Section: Discussionmentioning
confidence: 99%
“…There are two scenarios in which it is particularly important to assess genetic risk and consider genetic testing during survivorship: (1) in cancer survivors who meet criteria for genetic testing but have not yet had this performed, and (2) in cancer survivors who had genetic counseling and testing previously yet should now consider additional testing because of a new cancer diagnosis (personal or family) or updated testing options (e.g., availability of expanded molecular analyses).…”
mentioning
confidence: 99%